PENGARUH PERBEDAAN JENIS ELEKTROLIT DAN KONSENTRASI TERHADAP SINTESIS GRAPHENE SECARA ELEKTROKIMIA MENGGUNAKAN REAKTOR SOLENOIDA - Nuriskasari, Isnanda; Handaya, Devi; Prayogi, Adila Syifa; Mustopa, In In; Sihombing, Tania Sonya; Ramadhan, Mochammad Tendi Noer (AUSTENIT, 2023)
Electrochemical synthesis of graphene is a way to obtain graphene. Graphene as a material that has thermal, magnetic, mechanical, chemical properties, especially in special electrical properties. The development of graphene lies in the method used, one of which is the electrochemical method, where this method has the advantages of being fast, environmentally friendly, and low cost in the production process. In the process, this method requires several main components, namely electrolytes, electrodes, and an electrical supply. The electrolytes used are still very diverse and the search for the right electrolyte continues to increase the production of graphene synthesis. This study focuses on knowing the effect of the Sulfuric Acid (H2SO4), Hydrochloric Acid (HCl), and Vinegar Acid (CH3COOH) as electrolytes in electrochemically obtaining graphene and the effect of electrolyte concentration (0.5M; 1M; and 1.5M). The fixed variable used is commercial graphite with the reactor used is a solenoid modified reactor with a reaction time of 1 hour. The result is that the electrolyte H2SO4 is a very good type of electrolyte in the graphene synthesis process compared to HCl and CH3COOH, it can be seen from a graph containing data in the form of graphite weight after the electrochemical graphene synthesis process, and the greater the concentration, the stronger the electrolyte in the graphene synthesis process, so that more graphite will be eroded and more graphene will be obtained.